+0  
 
0
113
2
avatar

Pouvez-vous résoudre ce avec le calcul étapes 2x ^ 2 + x-6 = 4x ^ 2-4x-3

Guest Apr 15, 2017
Sort: 

2+0 Answers

 #1
avatar
0

Solve for x:
2 x^2 + x - 6 = 4 x^2 - 4 x - 3

Subtract 4 x^2 - 4 x - 3 from both sides:
-2 x^2 + 5 x - 3 = 0

The left hand side factors into a product with three terms:
-(x - 1) (2 x - 3) = 0

Multiply both sides by -1:
(x - 1) (2 x - 3) = 0

Split into two equations:
x - 1 = 0 or 2 x - 3 = 0

Add 1 to both sides:
x = 1 or 2 x - 3 = 0

Add 3 to both sides:
x = 1 or 2 x = 3

Divide both sides by 2:
Answer: | x = 1                   or                    x = 3/2

Guest Apr 15, 2017
 #2
avatar+223 
0

 

 

x= 1 , x= 3/2. 

 

Utiliser la formule quadratique

Veteran  Apr 15, 2017
edited by Veteran  Apr 15, 2017

7 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details